CORRELATION OF ORGANIZATIONAL COMMITMENT, WORK MOTIVATION, AND EMPLOYEE PERFORMANCE: CASE STUDY AT THE DEPARTMENT OF COMMUNICATION, INFORMATICS, STATISTICS, AND ENCRYPTION, SOUTHWEST PAPUA PROVINCE - Darmawati Darmawati; Vebby Anwar; Mervin Irian Sadipun Komber (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
This study aims to analyze the correlation between organizational commitment, work motivation, and employee performance at the Department of Communication, Informatics, Statistics, and Encryption of Southwest Papua Province. The research employs a quantitative approach using a survey method involving 43 employees as respondents. Data were collected through questionnaires and analyzed using statistical software. The results indicate that both organizational commitment and work motivation have a positive and significant relationship with employee performance, both partially and simultaneously. These findings highlight the importance of strengthening organizational commitment and work motivation to enhance employee performance in newly established regional government agencies. The study recommends strategies for improving internal communication, fostering commitment, and enhancing work motivation to achieve optimal organizational goals.